CURRENT PRINCIPLES FOR CRANIOPHARYNGIOMA TREATMENT - A. N. Konovalov; M. A. Kutin; B. A. Kadashev; P. L. Kalinin; D. V. Fomichev; L. I. Astafyeva; A. V. Golanov; Yu. Yu. Trunin (Опухоли головы и шеи)
The paper describes the classification and treatment options of craniopharyngiomas, benign epithelial tumors arising from the cell remains of the Rathke’s pouch. It presents a few types of surgical accesses during surgical treatment for this disease and gives examples of how to place an Ommaya reservoir.